2002
DOI: 10.1016/s0928-8244(02)00393-0
|View full text |Cite
|
Sign up to set email alerts
|

A possible pitfall in the identification of Burkholderia mallei using molecular identification systems based on the sequence of the flagellin fliC gene

Abstract: Amotile Burkholderia mallei and motile Burkholderia pseudomallei display a high similarity with regard to phenotype and clinical syndromes, glanders and melioidosis. The aim of this study was to establish a fast and reliable molecular method for identification and differentiation. Despite amotility, the gene of the filament forming flagellin (fliC) could be completely sequenced in two B. mallei strains. Only one mutation was identified discriminating between B. mallei and B. pseudomallei. A polymerase chain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 29 publications
(42 reference statements)
3
26
0
1
Order By: Relevance
“…Thirteen B. pseudomallei reference strains and all six isolates from Thailand showed a 78A>C shift. The strain 844 and the isolates UE 16 and UE 19, which have the same fliC sequence as B. mallei strains as previously demonstrated [11], were identical regarding the rpsU sequence with the other investigated B. pseudomallei isolates with the 78A>C shift. Three to four mutations in the nucleotide sequence of the rpsU gene of B. thailandensis allow for a differentiation of this non-pathogenic saprophyte from the dangerous agents B. mallei and B. pseudomallei as well as from other pathogenic species as B. cepacia and B. gladioli.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Thirteen B. pseudomallei reference strains and all six isolates from Thailand showed a 78A>C shift. The strain 844 and the isolates UE 16 and UE 19, which have the same fliC sequence as B. mallei strains as previously demonstrated [11], were identical regarding the rpsU sequence with the other investigated B. pseudomallei isolates with the 78A>C shift. Three to four mutations in the nucleotide sequence of the rpsU gene of B. thailandensis allow for a differentiation of this non-pathogenic saprophyte from the dangerous agents B. mallei and B. pseudomallei as well as from other pathogenic species as B. cepacia and B. gladioli.…”
Section: Discussionsupporting
confidence: 74%
“…However, DNA-DNA-hybridization studies suggested that they are merely pathovars of one single species [9,10]. Sequence analysis of the gene of the filament-forming flagellin, fliC, corroborated this theory [11].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…There are several reports in the literature that describe PCR-based assays for identifying B. pseudomallei; however, none of the assays are currently being used for melioidosis diagnosis (Bauernfeind et al, 1998;Gee et al, 2003;Hagen et al, 2002;Holden et al, 2004;Lee et al, 2005;Sprague et al, 2002;Tanpiboonsak et al, 2004;Thibault et al, 2004;Tomaso et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports in the literature that have targeted the B. pseudomallei 16S and 23S rRNA, 16S-23S intergenic region, flagellin C (fliC), heat shock protein 70, and a type 3 secretion (TTS) system for the molecular identification of B. pseudomallei and possible differentiation from B. mallei (Antonov et al, 2004;Gee et al, 2003;Hagen et al, 2002;Lee et al, 2005;Sprague et al, 2002;Tanpiboonsak et al, 2004;Thibault et al, 2004;Tomaso et al, 2005;Tomaso et al, 2004;Tyler et al, 1995). Despite the numerous misleading titles in the literature (i.e., titles that imply B. mallei-specific), there are no B. mallei-specific molecular assays for discriminating this obligate mammalian pathogen from B. pseudomallei.…”
Section: Sponsor/monitor's Report Number(s)mentioning
confidence: 99%